1999
DOI: 10.1007/s006010050110
|View full text |Cite
|
Sign up to set email alerts
|

Proton Spin and Chiral Dynamics

Abstract: Chiral spin fraction models agree with the proton spin data only when the chiral quark-Goldstone boson couplings are pure spinflip. For axialvector coupling from soft-pion physics this is true for massless quarks, and at high momentum for light quarks. Axialvector quark-Goldstone boson couplings with constituent quarks are found to be inconsistent with the proton spin data.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…It is found that if we put p T = 0 in Eq. ( 4), this equation will be casted to its usual form while there is not finally any transverse momentum dependence in the χQM [14,15]. In this case the splitting function P jB/i and also the q j distribution are given by expressions which are used in Refs.…”
Section: The Bare Quark-gs Boson Vertexmentioning
confidence: 99%
“…It is found that if we put p T = 0 in Eq. ( 4), this equation will be casted to its usual form while there is not finally any transverse momentum dependence in the χQM [14,15]. In this case the splitting function P jB/i and also the q j distribution are given by expressions which are used in Refs.…”
Section: The Bare Quark-gs Boson Vertexmentioning
confidence: 99%
“…where m  is the mass of GS boson. If we take p T =0 in equation (4), the splitting function P j i  has no dependence on transverse momentum and the modified QM c is not, finally, transverse momentum dependent [39][40][41][42][47][48][49].…”
Section: Tmd Parton Distributions In the Modified Chiral Quark Modelmentioning
confidence: 99%